Sistem Informasi Akuntansi Dan Pengendalian Piutang Pada PT. KUSUMANTARA GRAHA JAYATRISNA - Murti, Ananta Raditya; Widodo, Arifin Puji; Sukmaaji, Anjik (Jurnal JSIKA, 2012)
PT. Kusumantara Graha Jayatrisna is Kusuma Agro Group subsidiaries engaged in architectural and civil. The company currently experiencing problems in terms of management control of cash flow. The planning of cash inflow from receivables record that 5.3% people are late paying between 1 to 30 days, 5.3% people are late paying between 31 to 60 days, 4.1% people are late paying between 61 to 90 days, and 5, 3% people are late paying more than 90 days. These problems can lead to the imbalance between cash inflows with cash out of the company. Based on that issues, made ​​accounting information systems and receivables controller in the form of a computer application that is able to control the receipt of cash from accounts receivable that are not experiencing delays. The application generate customer’s receivable information (cash receipts from accounts receivable statement, cash receipts plans of receivables statement, aging schedule report), corporate debt (cash expenditure statements, cash spending plans statements), cash flow plans statement, and profit and loss statement. With this system, cash receipts from receivables be on time, so that the problems of the imbalance between cash in and cash out of the company can be resolved. Keyword: accounting information systems, cash flow, account receivables